2011
DOI: 10.1097/prs.0b013e31820cf282
|View full text |Cite
|
Sign up to set email alerts
|

Voice Reconstruction with Free Ileocolon Flap Transfer: Implications for the Lower Respiratory Tract

Abstract: Reconstruction with the free ileocolon flap was shown to be a possible therapeutic option when considering the consequences on the lower respiratory tract. Aspiration was the main complication and was avoided by internal plication of the valve and by reduction of the ileocecal angle. Awareness of the nature of the bacterial flora colonizing the trachea and voice tube could be helpful in guiding the empirical antibiotic therapy in case of infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“…Consensual to the decrease of the absolute number of the goblet cells, a reduction in the volume of secretions from the voice tube was noticed in all patients soon after reconstruction, reducing the chances of aspiration through the tracheostomy site and risk of pneumonia. 10 The same phenomenon, interpreted as a protective adaptive mechanism, has been reported in the urinary reservoirs reconstructed with ileum. 4,5 Four factors probably played a critical role in producing the morphological changes of the ileal and cecal mucosa, namely, deprivation from the luminal nutrients and pancreatic and biliary secretions; decrease in the growth factors acting in autocrine, paracrine, or endocrine fashion; reduced workload of nutrient absorption; and chronic intermittent exposure to the airflow.…”
Section: Discussionmentioning
confidence: 75%
“…Consensual to the decrease of the absolute number of the goblet cells, a reduction in the volume of secretions from the voice tube was noticed in all patients soon after reconstruction, reducing the chances of aspiration through the tracheostomy site and risk of pneumonia. 10 The same phenomenon, interpreted as a protective adaptive mechanism, has been reported in the urinary reservoirs reconstructed with ileum. 4,5 Four factors probably played a critical role in producing the morphological changes of the ileal and cecal mucosa, namely, deprivation from the luminal nutrients and pancreatic and biliary secretions; decrease in the growth factors acting in autocrine, paracrine, or endocrine fashion; reduced workload of nutrient absorption; and chronic intermittent exposure to the airflow.…”
Section: Discussionmentioning
confidence: 75%
“…Fifteen studies reported the use of postoperative chemotherapy or radiotherapy (►Table 3). 12,13,15,[17][18][19][20][24][25][26][27][28][29]33,[35][36][37][38][39] Primary and secondary reconstructions were performed in 24.6 (n ¼ 134) and in 19.1% (n ¼ 104) of the cases, respectively (►Table 4). The surgical time ranged from 8 to 14.5 hours reported in four studies.…”
Section: Resultsmentioning
confidence: 99%
“…6 Moreover, the unconstrained peristalsis and the biologic secretions supply intestinal flaps with a natural self-cleansing machinery that prevents obstruction of the reconstructed phonation tube. 6,20,26 In contrast to the ICFF, fasciocutaneous and jejunal free flaps require a trachea-esophageal prosthesis to generate voice which ultimately results in increased morbidity. In fact, the incidence of leakage around a speech prosthetic valve following TEP enlargement is acknowledged to be between 1 and 29% with a 3-fold increased risk of aspiration pneumonia, a 20 to 30% mortality rate, and 14% long-lasting requirements of nutritional support via percutaneous gastrostomy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 In the last decade, our group has conducted a significant number of aerodigestive track reconstructions using free and pedicle bowel flaps. 8,12,13,[18][19][20] Even though the success rate of these flaps is high, 6 we have noticed that when a ischemic event occurs, the portion of the bowel conduit that survives is usually the one not covered by serosa (e.g., posterior wall of the terminal ileum and ascending colon). However, and up to now, no study has demonstrated this physiological process among bowel conduits with and without serosa during ischemic events.…”
Section: Discussionmentioning
confidence: 99%